(untitled) - 1928-; Bunting, Eve; Himler, Ronald (New York, 1990)
A boy and his father come from far away to visit the Vietnam War Memorial in Washington and find the name of the boy's grandfather, who was killed in the conflict.
Keywords: Vietnam Veterans Memorial (Washington, D.C.); Fiction; Vietnam Veterans Memorial; Fiction